2007
DOI: 10.1002/cmdc.200700050
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Asymmetry in Fingerprint Similarity Searching is a Direct Consequence of Differences in Bit Densities and Molecular Size

Abstract: Recently, systematic similarity calculations using Tversky coefficients have suggested that putting higher weight on bit settings of active reference molecules (templates) than database compounds increases hit rates in similarity searching using 2D fingerprints. These findings have been interpreted as evidence for "asymmetry" in chemical similarity searching. We have thoroughly analyzed this phenomenon and demonstrate that apparent asymmetry in similarity search calculations is a direct consequence of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…Furthermore, Tc was shown to be the coefficient of choice in similarity searching when reference and database molecules had comparable complexity, but when these complexity levels varied, other coefficients were preferred [76]. Finally, an apparent asymmetry of Tversky similarity values observed in database searching [77] could also be directly attributed to complexity effects [78]. Clearly, circumventing complexity effects is not only of scientific interest but also of high relevance for practical applications.…”
Section: Circumventing Intrinsic Limitations: Complexity Effectsmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, Tc was shown to be the coefficient of choice in similarity searching when reference and database molecules had comparable complexity, but when these complexity levels varied, other coefficients were preferred [76]. Finally, an apparent asymmetry of Tversky similarity values observed in database searching [77] could also be directly attributed to complexity effects [78]. Clearly, circumventing complexity effects is not only of scientific interest but also of high relevance for practical applications.…”
Section: Circumventing Intrinsic Limitations: Complexity Effectsmentioning
confidence: 95%
“…As a complexity-independent fingerprint representation, PDR-FP has been reported [32] that generates a constant bit density of 93/500 for all compounds, as described above. Thus, similarity search calculations with PDR-FP are not biased by differences in molecular complexity [78] and have been shown to be particularly effective on compound classes having high structural diversity where other types of fingerprints produce only low compound recall [32,80]. Furthermore, it has recently also been demonstrated that conventional keyed fingerprints can be rendered complexity-independent through 'balanced codes' transformation, that is, by merging a fingerprint with the complement of its bit setting, which generates a constant bit density of 50% (but doubles the size of the fingerprint) [81].…”
Section: Circumventing Intrinsic Limitations: Complexity Effectsmentioning
confidence: 99%
“…In addition to uncertainties associated with the interpretation of calculated similarity values, molecular complexity or size effects are known to bias fingerprintbased similarity evaluation and negatively affect search performance [6,22,42,43]. In a milestone publication, Flower demonstrated that reference molecules of increasing size generate systematically higher Tc values in databases searching [6].…”
Section: Intrinsic Caveatsmentioning
confidence: 97%
“…The Tversky coefficient can be biased towards substructure similarity. The Tversky coefficient is defined as virtual screening recall -a value which has been found to also be beneficial in similarity searching using fingerprints 28,29 , and has also shown potential in scaffold hopping with fingerprints 30 . …”
Section: Repeat Steps 2 and 3 Until The Set Is Emptymentioning
confidence: 99%